Understanding Toxoplasma gondii genetic diversity in Benin through its hosts and genomics : human and environmental influences - (:unkn) unknown (My University, 2020)
Through international trades, Europe, Africa and South America share a long history of exchanges, potentially associated with exchanges of pathogens. We used Toxoplasma gondii, the worldwide parasite with a geographical structuration of its global population to study the influence of colonial trade on T. gondii genetic diversity in West-African countries. Previous data from Senegal showed a clear influence of Europe on the diversity on the coastal area. We therefore decided to study T. gondii genetic diversity in Benin, another West-African country with a more intense colonial history. By isolating T. gondii strains from domestic animals (from poultry, good bioindicators of the parasite presence in an environment) but also from DNA detected in rodents (preferred preys of felids) captured in Cotonou, we showed a predominance of the Africa 1 genotype by 15 microsatellites genotyping all over Benin, an autochtonous genotype highly virulent in certain rodent species. With population genetics analyses on these samples, we could imagine the recent evolutive history and how the actual parasite population structure and hosts were influenced in that part of Africa. However, the triangular trade continued to South America and especially Brazil where the Africa 1 genotype was also detected. The genome analyses of non-Africa 1 Brazilian strains suggested potential Africa 1 portions introgressions in their genome. That would be the result of the extensive exchanges during the slave trade and would have an impact today on the parasite virulence and in particular on human toxoplasmosis. The continuing work sould focus on studying the Beninese rodents immunology response against T. gondii, the study of T. gondii genomes with the idea to elucidate the past and recent evolutive histories of the parasite and how it is relate to human toxoplasmosis.
Keywords: African Research